Curvature variation along the tropomyosin molecule - Li, Xiaochuan (Edward); Lehman, William; Fischer, Stefan; Holmes, Kenneth C. (Journal of structural biology, 2010)
Complementarity between the tropomyosin supercoil and the helical contour of actin-filaments is required for the binding interaction of actin and tropomyosin (Li et al., 2010). Clusters of small alanine residues in place of canonical leucines along coiled-coil tropomyosin may be responsible for pre-shaping tropomyosin and promoting conformational complementarity to F-actin. A longitudinal displacement between the two chains of the tropomyosin coiled-coil induced by the alanine clusters could produce localized bending or limited flexibility along tropomyosin needed to shape tropomyosin (Brown and Cohen, 2005). To evaluate the influence of alanine clusters on tropomyosin curvature, we calculated the longitudinal displacement between amino acid residues on adjacent chains of the tropomyosin coiled-coil and related this “Z-displacement” to the position of the alanine clusters. Measurements were made on high-resolution crystal structures of tropomyosin fragments and on trajectories from molecular dynamics simulations of full-length αα-tropomyosin. We found no strict one-for-one spatial correlation between alanine cluster position and the Z-displacement. Neither did we find any direct correspondence between the clusters and the local curvature of tropomyosin. Rather than just causing specific local structural effects, the overall influence of alanine clusters is complex and delocalized, leading to a gradually changing bending pattern along the length of tropomyosin.